2016
DOI: 10.1016/j.jhep.2016.01.013
|View full text |Cite
|
Sign up to set email alerts
|

IL-23 prevents IL-13-dependent tissue repair associated with Ly6C lo monocytes in Entamoeba histolytica -induced liver damage

Abstract: The IL-23/IL-17 axis plays a critical role in the immunopathology of hepatic amebiasis. IL-13 secreted by CD11b(+)Ly6C(lo) monocytes may be associated with recovery from liver damage. An IL-13/anti-IL13-mAb complex mimics this function, suggesting a novel therapeutic option to support tissue healing after liver damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 38 publications
(54 reference statements)
1
18
0
Order By: Relevance
“…Although the mouse model for ALA, has some limitations regarding the artificial route of infection, it is well established [2325] and allows in this study to discriminate between pathogenic and less pathogenic clones. Accordingly, the high reproducibility of the differences in the recovery time of the liver between „non-pathogenic”and „pathogenic” E .…”
Section: Discussionmentioning
confidence: 99%
“…Although the mouse model for ALA, has some limitations regarding the artificial route of infection, it is well established [2325] and allows in this study to discriminate between pathogenic and less pathogenic clones. Accordingly, the high reproducibility of the differences in the recovery time of the liver between „non-pathogenic”and „pathogenic” E .…”
Section: Discussionmentioning
confidence: 99%
“…At the age of 12–14 weeks male and female C57BL/6 mice were intrahepatically infected as previously described 31 , 66 with 2 × 10 5 in vitro-cultured E. histolytica trophozoites of the highly pathogenic clone B2, generated from the cell line B (HM-1:IMSS) 31 .…”
Section: Methodsmentioning
confidence: 99%
“…cd T cells are the main source of IL-17 in many diseases, particularly in the early phases. 33,34 The IL-23/IL-17 axis plays an important role in experimental autoimmune encephalomyelitis, rheumatoid arthritis and inflammatory bowel disease models in mice. The IL-17 + cd T cells can promote IL-17 production from CD4 + T cells to amplify the loop of IL-17 production and exacerbate experimental autoimmune encephalomyelitis.…”
Section: Introductionmentioning
confidence: 99%
“…31,32 Interleukin-23 also promotes Th17 cell survival and IL-17A, IL-17F and IL-22 secretion. 33,34 The IL-23/IL-17 axis plays an important role in experimental autoimmune encephalomyelitis, rheumatoid arthritis and inflammatory bowel disease models in mice. 30,35,36 Our early research results have demonstrated that cd T cells, especially Vc4 cd T cells, can suppress the production of IFN-c by NKT cells by secreting IL-17A in Con A-induced liver injury.…”
Section: Introductionmentioning
confidence: 99%